2020
DOI: 10.1007/s00467-020-04875-y
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder and kidney disease

Abstract: Neurodevelopmental impairments have been recognised as a major association of paediatric kidney disease and bladder dysfunction, presenting challenges to clinicians and families to provide reasonable adjustments in order to allow access to investigations and treatments. Autism spectrum disorder (ASD) is a common neurodevelopmental disorder characterised by impairments in social interaction/communication and repetitive sensory-motor behaviours. Mental health, learning and physical co-morbidities are common. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Within body-site clustering of fecal meta-signatures of 34 different conditions, studied by at least 2 studies in BugSigDB and generated from 504 signatures of increased relative abundance in the study group, revealed similarities in reported differential abundance patterns between disease phenotypes (Figure 5B). This included similarities in microbial shifts for (i) HIV infection and different gastrointestinal cancers, both characterized by chronic inflammation of the GI tract and microbial signatures that point to shared pathogenic pathways including tryptophan catabolism and butyrate synthesis 79 , (ii) chronic kidney disease and autism, linked through deleterious copy number variants 80,81 and pathogenic gut microbiota-derived metabolites produced by species of the Clostridia class 82,83 , and (iii) type 2 diabetes and schizophrenia, consistent with observations that people with schizophrenia are at increased risk of type 2 diabetes, and conversely, that traditional risk factors for type 2 diabetes are common in people with schizophrenia and can affect the gut microbiome, especially obesity, poor diet, and sedentary lifestyle 84 . A strong enrichment of genera of the Clostridia class drove the similarity between the meta-signatures of Hashimoto’s thyroiditis (12 out of 14 genera, 85.7%, p -value = 2.1 · 10 −05 , proportion test) and chronic fatigue syndrome (11/17, 64.7%, p -value = 0.003).…”
Section: Resultsmentioning
confidence: 99%
“…Within body-site clustering of fecal meta-signatures of 34 different conditions, studied by at least 2 studies in BugSigDB and generated from 504 signatures of increased relative abundance in the study group, revealed similarities in reported differential abundance patterns between disease phenotypes (Figure 5B). This included similarities in microbial shifts for (i) HIV infection and different gastrointestinal cancers, both characterized by chronic inflammation of the GI tract and microbial signatures that point to shared pathogenic pathways including tryptophan catabolism and butyrate synthesis 79 , (ii) chronic kidney disease and autism, linked through deleterious copy number variants 80,81 and pathogenic gut microbiota-derived metabolites produced by species of the Clostridia class 82,83 , and (iii) type 2 diabetes and schizophrenia, consistent with observations that people with schizophrenia are at increased risk of type 2 diabetes, and conversely, that traditional risk factors for type 2 diabetes are common in people with schizophrenia and can affect the gut microbiome, especially obesity, poor diet, and sedentary lifestyle 84 . A strong enrichment of genera of the Clostridia class drove the similarity between the meta-signatures of Hashimoto’s thyroiditis (12 out of 14 genera, 85.7%, p -value = 2.1 · 10 −05 , proportion test) and chronic fatigue syndrome (11/17, 64.7%, p -value = 0.003).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have previously shown that kidney disease was associated with cardiovascular risk factors in our study ASD + ID population (Miot et al, 2019). In addition, several recent studies have highlighted putative genetic vulnerability to kidney disease in ASD as early as in childhood (Clothier & Absoud, 2021), which may be compounded by cardiovascular diseases and ageing itself.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, seven DEGs (Crym, Ctss, Fasn, Fcgrt, Gabrb3, Lyz2, and Vcam1) were found to be associated with kidney diseases, including renal inflammation, crescentic glomerulonephritis or end-stage renal failure. Interestingly, population-based studies support that autism spectrum disorder (ASD) and kidney disease coexist in several genetic disorders (for review see Table 2 in (33)), suggesting that the same genetic modification can affect neurodevelopment and nephrogenesis. However, because the genetic alterations (deletion or duplication) associated with these disorders often encompass several genes, it is still unclear how these genes contribute to the underlying molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%